The Effects of Nanosilver (Nanocid®) on Survival Percentage of Rainbow Trout (Oncorhynchus mykiss) - Shahbazzadeh, Delavar; Ahar, Hamed; Rahimi, Narges Mohammad; Dastmalchi, Farhad; Soltani, Mahdi; Rahmannya, Jafar; Khorasani, Neda; Fotovat, Mansour (Pakistan Journal of Nutrition, 2009)
Nano materials have unique antimicrobial properties. The toxic level of nanosilver, with the commercial name of Nanocid was studied. Rainbow trout (Oncorhynchus mykiss) with median weight of 1.049 g, was treated with 1, 2, 5, 10 and 20 ppm of nanosilver. The results were analyzed after 24, 48, 72, and 96 h and the lethality dose obtained between 1.25-10 ppm. In conclusion, the 48, 72 and 96-h median lethal concentrations (LC50) of nanosilver tests were obtained at 3.5, 3 and 2.3 mg/L, respectively, indicating moderate toxicity of nanocid in rainbow trout fish.